2003
DOI: 10.1002/cncr.11261
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ultrasonographic identification of the sentinel lymph node in patients with malignant melanoma

Abstract: BACKGROUND Dissection of the “sentinel lymph node” (SLN) as identified by lymphoscintigraphy is becoming increasingly important in the treatment of patients with malignant melanoma. The purpose of the current study was to determine whether the SLN also could be identified by ultrasound. METHODS Sixty‐seven patients with malignant melanoma (40 females and 27 males, with an average age of 48.8 years) in whom extirpation of the SLN was indicated underwent ultrasonography of the regional lymph nodes prior to preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…These features have been well described previously. [7][8][9] In a recent study by Kahle et al, 15 a specific asymmetrical cortical thickening phenomenon causing a ''cap''-like sonomorphological pattern to occur on US in the SLNs of melanoma patients was described. The locations of any lymph nodes found to show this cap phenomenon on US were compared with the location of nodes subsequently determined to be the SLNs by lymphoscintigraphy.…”
Section: Discussionmentioning
confidence: 97%
“…These features have been well described previously. [7][8][9] In a recent study by Kahle et al, 15 a specific asymmetrical cortical thickening phenomenon causing a ''cap''-like sonomorphological pattern to occur on US in the SLNs of melanoma patients was described. The locations of any lymph nodes found to show this cap phenomenon on US were compared with the location of nodes subsequently determined to be the SLNs by lymphoscintigraphy.…”
Section: Discussionmentioning
confidence: 97%
“…6 The value of HRUS for staging of patients with melanoma as an inexpensive and noninvasive imaging method has been well documented in several studies in the past. [7][8][9][10][11] However, knowledge about sonographic appearance of nontumor affected peripheral LNs is rather marginal. Just a few past publications examined this issue.…”
mentioning
confidence: 97%
“…At initial melanoma staging, in patients scheduled for SLNB, we do not try to recognize where and which are the sentinel lymph nodes. Kahle et al 30 identified a specific sonographic pattern of sentinel lymph nodes and found a high correlation with lymphoscintigraphic findings, particularly for inguinal sentinel nodes. These authors noted that the sentinel nodes had asymmetric thickening of the cortex (the "cap," making the hyperechoic hilum eccentric) in the longitudinal view, whereas the nonsentinel nodes had a symmetric cortical thickness (ie, centrally located hyperechogenicity).…”
mentioning
confidence: 99%